2021
DOI: 10.1590/0100-29452021014
|View full text |Cite
|
Sign up to set email alerts
|

Sample size for postharvest quality traits of ‘Palmer’ mangoes

Abstract: The objective of this study was to determine the most efficient sample size required to estimate the mean of postharvest quality traits of ‘Palmer’ mangoes harvested in two growing seasons. A total of 50 mangoes were harvested at maturity stage 2, in winter (June 2020) and spring (October 2020), and evaluated for weight, length, ventral and transverse diameter, skin and pulp L*, C* and hº, dry matter, firmness, soluble solids (SS), titratable acidity (TA) and the SS/TA ratio. According to the results, the coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, the skin color may not have a good relationship with the internal quality of the fruit in some mango varieties [40]. In this context, pulp color changes are uniform during fruit ripening, so it is considered an adequate maturity index for mangoes [41]. Skin and pulp hue angles decreased as the duration of storage increased, which confirms color changes typical of mango ripening.…”
Section: Discussionmentioning
confidence: 99%
“…However, the skin color may not have a good relationship with the internal quality of the fruit in some mango varieties [40]. In this context, pulp color changes are uniform during fruit ripening, so it is considered an adequate maturity index for mangoes [41]. Skin and pulp hue angles decreased as the duration of storage increased, which confirms color changes typical of mango ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit quality is defined by appearance, flavor, texture, and nutritional properties, which might be affected by several factors, including environmental conditions, crop management practices, maturity stage at harvest, storage conditions and genotype [4]. Fruit quality is measured through physical and chemical properties, which can also be used to characterize maturity stage and indicate when fruit are ready for consumption [5].…”
mentioning
confidence: 99%
“…Indeed, studies have shown that fruit with higher DMC have higher consumer acceptance (FREITAS et al, 2022). However, the methods used to measure DMC and SSC are destructive, time consuming, and require sample processing and manual labor (MARQUES et al, 2016;VILVERT et al, 2021).…”
mentioning
confidence: 99%